An empirical analysis of the efficiency determinants in the Southern African electricity sector: evidence and policy implications. Issue 1 (2nd January 2018) - Barabutu, Jerold; Lee, Hyunjung
Abstract: The on-going electricity sector reforms in Southern Africa aim to improve the technical performance of incumbent state-owned electric companies. Despite the reforms, these companies do not always satisfactorily meet the growing demand for electricity distribution. As a result, there is a clear need for in-depth analysis on the performance of these companies. Against this backdrop, we assessed the relative efficiency of twelve (12) state-owned electric companies operating in Southern African Power Pool (SAPP) during the period of 2004–2015 using Data Envelopment Analysis (DEA) window analysis. In the second stage, we boostrapped the efficiency scores with a truncated regression. According to the analyses, regional efficiency improvements have been limited. Moreover, the results revealed that natural monopoly, GDP per capita, company age, and country size all have a statistically significant impact on companies' efficiency. However, government ownership does not affect the efficiency of companies. To this respect, policy implications were suggested to enhance regional technical efficiency.